Degradation mechanism of planar-perovskite solar cells: correlating evolution of iodine distribution and photocurrent hysteresis - Ginting, Riski Titian; Jeon, Mi-Kyoung; Lee, Kwang-Jae; Jin, Won-Yong; Kim, Tae-Wook; Kang, Jae-Wook (ROYAL SOC CHEMISTRY, 2017)
In this report, we demonstrate that moisture/O-2 in ambient air is the major issue for the photovoltaic performance degradation and severe photocurrent hysteresis of non-encapsulated planar-perovskite solar cells. Consequently, this leads to difficulty in determining the real power conversion efficiency (PCE). Upon longer storage time, the evidence of a small amount of iodine in the hole transport layer (HTL) led to hindering the charge transport from the HTL to the anode, thus resulting in the decrease of short-circuit current density and fill factor. Meanwhile, the transient chronoamperometry result suggests that the increase of hysteresis with storage time is ascribed to the changes of activation energy. It is further supported by X-ray photoelectron spectroscopy depth profile analysis, which revealed that penetration of moisture/O-2 caused the shifts of iodine distribution within the perovskite layer after aging time of >72 h. Remarkably, effective moisture/O-2 passivation can be achieved by combination of polyimide and UV-cured polymer as a novel encapsulation process, which exhibited an impressive stabilized PCE of above 14% (retained 97% of its initial efficiency) and simultaneously maintained the hysteresis up to similar to 1000 h.
Keywords: LEAD IODIDE; THIN-FILMS; ANOMALOUS HYSTERESIS; SELECTIVE CONTACTS; HIGHLY EFFICIENT; HIGH-PERFORMANCE; SPIRO-MEOTAD; STABILITY; TEMPERATURES; INSTABILITY